Quantum secret sharing by using Fourier transform on orbital angular momentum. (1st March 2019) - Qin, Huawang; Tso, Raylin; Dai, Yuewei
Abstract : A quantum secret sharing scheme based on orbital angular momentum (OAM) is proposed. The dealer generates single particles in OAM basis or angular position (ANG) basis randomly. The participants encode their private keys into the particles through performing quantum Fourier transforms. Then the dealer can use the single‐particle measurements to get the shared secret. In the authors' scheme, the secret is protected by the distinguishability of OAM basis and ANG basis. Compared to the traditional two‐dimensional schemes, the authors' scheme can use the higher dimension of OAM to increase the detecting rate of eavesdropping, and enhance the security in practice. Besides, only the single particles are needed in their scheme. Compared to the schemes based on entangled particles, the authors' scheme will be more practical with the present technology.